1981
DOI: 10.1111/j.1476-5381.1981.tb09117.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Muscarine on the Longitudinal Muscle of the Guinea‐pig Isolated Ileum

Abstract: dl‐Muscarine elicited a contraction of the ileal longitudinal muscle of the guinea‐pig and the contraction was characterized by an after‐response. Physostigmine (2.0 × 10−8 m) potentiated the contraction of the longitudinal muscle elicited by dl‐muscarine. Hemicholinium‐3 (HC‐3) caused a rightward shift of the dose‐response curve to dl‐muscarine on the ileal longitudinal muscle of the guinea‐pig ileum. β‐Bungarotoxin (10 μg/ml) significantly (P < 0.025) reduced the contraction elicited by dl‐muscarine (2.5 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The present study validates the findings of Lurie et al 66 that the poisonings by Inocybe species is associated with constriction of pupils, muscle spasms, diarrhoea, slowing of heartbeat and a drop in blood pressure. In a study carried out by Ochillo et al 67 , it was demonstrated that muscarine elicited a contraction of ileal longitudinal muscles. This could possibly explain the increase in defecation (Fig.…”
Section: Effect Of In Vitro Digestion On Muscarinementioning
confidence: 96%
“…The present study validates the findings of Lurie et al 66 that the poisonings by Inocybe species is associated with constriction of pupils, muscle spasms, diarrhoea, slowing of heartbeat and a drop in blood pressure. In a study carried out by Ochillo et al 67 , it was demonstrated that muscarine elicited a contraction of ileal longitudinal muscles. This could possibly explain the increase in defecation (Fig.…”
Section: Effect Of In Vitro Digestion On Muscarinementioning
confidence: 96%
“…The A subunit has 120 amino acids and the B subunit has 60 amino acids giving a combined molecular weight of 21,800 Da (Rowan, 2001). Blockage of muscarinic receptors by b-B has been reported by Ochillo et al (1981).…”
Section: Choice Of Bungarotoxinsmentioning
confidence: 96%
“…The experiment was performed to assess the effect of LP extract on ileum contraction using isolated ileum of guinea pig [9]. Male guinea pig was killed and the ileum was rapidly removed and transferred to a dish containing Tyrode's solution aerated with 95% O 2 and 5% CO 2 , at 37°C.…”
Section: Bioassay Of Cholinergic Activity Of Lp Extracts Using Isolated Guinea Pig Ileummentioning
confidence: 99%